Representasi Sejarah, Budaya Dan Ekonomi Dalam Novel Runtuhnya Menara Azan Karya Yanti Soeparmo - Randa Anggarista; Riskin Tiara (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2022)
This study uses a new historicism approach with the aim of describing historical, cultural and economic representations in Yanti Soeparno's novel Runtuhnya Menara Azan. The data in this study are in the form of language units that reflect historical, cultural and economic representations. The data source in this study is the novel Runtuhnya Menara Azan by Yanti Soeparmo, published by Mizan Pustaka in 2009. The instrument in this research is the author himself who is oriented towards research on historical, cultural and economic representations, in the novel Runtuhnya Menara Azan by Yanti Soeparmo. . The data collection technique in this study was carried out by reading and note-taking techniques. The data analysis technique is carried out with the stages of categorization, presentation, and drawing conclusions. The results show that first, in Yanti Soeparmo's novel Runtuhnya Menara Azan, there is a reflection of Indonesian history regarding the theft and mass massacres committed by the Bumiputera people against the Europeans who had taken over the people's rights. Second, the cultural representation in Yanti Soeparmo's novel Runtuhnya Menara Azan is western culture which includes the use of language and class division of the Bumipuetra people. Third, the economic representation depicted in Yanti Soeparmo's novel Runtuhnya Menara Azan is a weak economic condition that causes people to suffer and the emergence of various types of diseases, such as starvation to death.